Assessing benefits and risks of incorporating plastic waste in construction materials - Cirino, Erica; Curtis, Sandra; Wallis, Janette; Thys, Tierney; Brown, James; Rolsky, Charles; Erdle, Lisa M. (Frontiers in Built Environment, 2023)
Plastic pollution and climate change are serious and interconnected threats to public and planetary health, as well as major drivers of global social injustice. Prolific use of plastics in the construction industry is likely a key contributor, resulting in burgeoning efforts to promote the recycling or downcycling of used plastics. Businesses, materials scientists, institutions, and other interested stakeholders are currently exploring the incorporation of plastic waste into building materials and infrastructure at an accelerated rate. Examples include composite asphalt-plastic roads, plastic adhesives, plastic-concrete, plastic/crumb rubber turf, plastic lumber, plastic acoustic/thermal insulation, plastic-fiber rammed earth, and plastic soil reinforcement/stabilizers. While some believe this to be a reasonable end-of-life scenario for plastic waste, research shows such efforts may cause further problems. These uses of plastic waste represent an ongoing effort at “greenwashing,” which both delays and distracts from finding real solutions to the plastic pollution crisis. Hypothesized effects of incorporating plastic waste in construction materials, including economic, environmental, human health, performance, and social impacts, are evaluated in this mini review. We compare known impacts of these treatments for plastic waste and provide recommendations for future research. Evidence shows that such practices exacerbate the negative ecological, health, and social impacts of plastic waste and increase demand for continued production of new (virgin) plastics by creating new markets for plastic wastes. We urge caution—and more research—before widely adopting these practices.